Register Variation in the New Testament Petrine Texts - Liu, Chiaen, (Linguistic Biblical Studies ;, 2022)
This book examines the nature of the early church from a Petrine perspective, employing an analysis of register to implement a more synthetic study of relevant texts in the New Testament. Liu utilises a type of discourse analysis that provides a framework for classifying grammatical and lexical information so that the reader can better understand the social function of not only Peter's speeches in Acts, but also the two epistles attributed to him. Liu's original and detailed study looks at the content and structure of the texts to enhance our understanding of the early church, with particular attention paid to the dichotomy between Petrine and Pauline Christianity and their competing pictures of Christian origins. This book will interest all scholars and students who wish to extend their understanding of both the historical and literary Peter.